Sebelum Upload Strategi Program Acara NATL (Night at The Library) Dalam Upaya Menarik Pengunjung Untuk Datang ke Perpustakaan Jakarta: Strategi Program Acara NATL (Night at The Library) Dalam Upaya Menarik Pengunjung Untuk Datang ke Perpustakaan Jakarta - Andriani, Melati (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2024)
Jakarta Library, as a strategic public institution in supporting literacy and education, faces significant challenges in the digital era, especially with the decline in the number of visitors due to easy access to digital resources. To address this, the library launched the Night at The Library (NATL) program, an innovative initiative aimed at attracting visitors, especially the younger generation. NATL is designed to transform the image of the library into a dynamic and multifunctional public space, by offering various interactive activities outside of regular operating hours, such as literacy discussions and art performances. Through a friendly, modern approach, NATL seeks to revive public interest in libraries and revive a culture of literacy. This study uses a qualitative approach with a constructivism paradigm and Peter K. Pringle's program management theory. The results show that the application of Pringle's theory in the planning, production, execution, and evaluation of the NATL program plays an important role in the success of the event. Planning includes strategies for selecting popular speakers, promotion through social media, and budget collaboration. NATL production adheres to structured management principles, involving the management of human and technical resources. Program execution ensures the optimization of library facilities, including accessibility for visitors with disabilities. The program evaluation recommended increasing the duration of book talk sessions, providing special tickets for library members, and providing rewards for active visitors. Overall, the NATL program has proven effective in attracting visitors, creating interactive experiences, and strengthening the role of libraries as centers of literacy and learning amidst the development of digital technology. Keywords: Event Program Strategy, NATL, Jakarta Library, Peter K Pringle